Penerapan Metode EOQ, POQ dan Analisis ABC dalam pengendalian persediaan bahan baku Coffee Shop - Akhtar, Muhammad Abid; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze inventory control for raw materials at Lini Kopi Surabaya by applying the Economic Order Quantity (EOQ), Period Order Quantity (POQ), and ABC Analysis methods. The study uses historical purchasing and usage data from May 2024 to April 2025. The research process includes data collection, material classification using ABC analysis, and calculation of economic order quantities, safety stock, reorder points, order frequency, and total inventory costs using EOQ and POQ methods. Results show that several materials fall into Category A and require stricter control. EOQ and POQ methods provide more efficient inventory costs compared to the company's current method. This study recommends the best method to reduce stockout risks and improve overall cost efficiency.